Under Glass Weathering of Hemp Fibers Reinforced Polypropylene Biocomposites: Degradation Mechanisms Based on Emitted Volatile Organic Compounds - Célia Badji; Célia Badji; Jean-Marc Sotiropoulos; Joana Beigbeder; Hélène Garay; Anne Bergeret; Jean-Charles Bénézet; Valérie Desauziers (Frontiers in Materials, 2020)
The durability of hemp fibers reinforced polypropylene biocomposites was investigated after one year under glass exposure. Volatile organic compounds emissions were assessed using a new passive sampling method. Degradation pathways were examined in order to understand the weathering mechanisms. The polymer matrix was decomposed into oxygenated products due to UV rays and high temperatures. As regards hemp fibers, different degradation steps of the carbohydrates were highlighted according to the nature of the detected furans. At a non-weathered state, dehydrations preceded the ring-opening mechanism, often catalyzed by Maillard reactions. The further cyclization induced the formation of 2- or 5-substituted furans emitted by non-weathered materials. Reactions between identified products after weathering which were not yet found in literature were proposed in this paper. They often implied a keto-enol tautomerism but also dehydrations that induced the formation of 3- and 4-substituted furanones. These differences can be explained by a primary decomposition of carbohydrates favored at a non-weathered state and a secondary one occurring at a weathered state.